2019
DOI: 10.2196/15320
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated With Facebook Use and Interest in Digital Disease Support Among Older Adults With Atrial Fibrillation: Cross-Sectional Analysis of Baseline Data From the Systematic Assessment of Geriatric Elements in Atrial Fibrillation (SAGE-AF) Cohort

Abstract: BackgroundOnline support groups for atrial fibrillation (AF) and apps to detect and manage AF exist, but the scientific literature does not describe which patients are interested in digital disease support.ObjectiveThe objective of this study was to describe characteristics associated with Facebook use and interest in digital disease support among older patients with AF who used the internet.MethodsWe used baseline data from the Systematic Assessment of Geriatric Elements in Atrial Fibrillation (SAGE-AF), a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…While frequency of sharing Stories, commenting, and posting about diet, exercise, or weight were associated with program interest in crude regression models, they were no longer statistically significant after controlling for post frequency, likely because women who posted also shared Stories, commented, and posted about GWG-related topics more often. These findings are similar to previous research assessing interest in digital health interventions among pregnant women ( 5 ) and non-pregnant adults ( 18 , 25 ) that found that participants who engaged in online health information-seeking and used social media more frequently were more likely to report high interest in digital interventions. Together, available evidence suggests that social media-delivered health interventions may be best suited for those already engaged in managing their health on these platforms.…”
Section: Discussionsupporting
confidence: 88%
“…While frequency of sharing Stories, commenting, and posting about diet, exercise, or weight were associated with program interest in crude regression models, they were no longer statistically significant after controlling for post frequency, likely because women who posted also shared Stories, commented, and posted about GWG-related topics more often. These findings are similar to previous research assessing interest in digital health interventions among pregnant women ( 5 ) and non-pregnant adults ( 18 , 25 ) that found that participants who engaged in online health information-seeking and used social media more frequently were more likely to report high interest in digital interventions. Together, available evidence suggests that social media-delivered health interventions may be best suited for those already engaged in managing their health on these platforms.…”
Section: Discussionsupporting
confidence: 88%
“…With older adults increasingly engaging with technology and telehealth visits, 22 opportunities for mHealth assessments are expanding. 23 Several studies have captured single components of a geriatric assessment, such as fall risk and depression, in the context of disease management 409 410 411 412 413 414 415 416 417 418 419 420 421 422 423 424 425 426 427 428 429 430 431 432 433 434 435 436 437 438 439 440 441 442 443 444 445 446 447 448 449 450 451 452 453 454 455 456 457 458 459 460 461 462 463 464 465 466 467 468 469 470 471 472 473 474 475 476 interventions. [24][25][26] However, remote administration of a more complete geriatric assessment remains an untapped resource for surveillance and identification of patients at high risk for poor medication adherence and disease management.…”
Section: Discussionmentioning
confidence: 99%
“…With older adults increasingly engaging with technology and telehealth visits, 22 opportunities for mHealth assessments are expanding. 23 Several studies have captured single components of a geriatric assessment, such as fall risk and depression, in the context of disease management interventions. 24 , 25 , 26 However, remote administration of a more complete geriatric assessment remains an untapped resource for surveillance and identification of patients at high risk for poor medication adherence and disease management.…”
Section: Discussionmentioning
confidence: 99%